Evaluation of Antioxidant, Anti-Inflammatory and Cytoprotective Properties of Ethanolic Mint Extracts from Algeria on 7-Ketocholesterol-Treated Murine RAW 264.7 Macrophages - Fatiha Brahmi; Thomas Nury; Meryam Debbabi; Samia Hadj-Ahmed; Amira Zarrouk; Michel Prost; Khodir Madani; Lila Boulekbache-Makhlouf; Gérard Lizard (MDPI AG, 2018)
The present study consisted in evaluating the antioxidant, anti-inflammatory and cytoprotective properties of ethanolic extracts from three mint species (Mentha spicata L. (MS), Mentha pulegium L. (MP) and Mentha rotundifolia (L.) Huds (MR)) with biochemical methods on murine RAW 264.7 macrophages (a transformed macrophage cell line isolated from ascites of BALB/c mice infected by the Abelson leukemia virus). The total phenolic, flavonoid and carotenoid contents were determined with spectrophotometric methods. The antioxidant activities were quantified with the Kit Radicaux Libres (KRLTM), the ferric reducing antioxidant power (FRAP) and the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. The MS extract showed the highest total phenolic content, and the highest antioxidant capacity, while the MR extract showed the lowest total phenolic content and the lowest antioxidant capacity. The cytoprotective and anti-inflammatory activities of the extracts were quantified on murine RAW 264.7 macrophages treated with 7-ketocholesterol (7KC; 20 µg/mL: 50 µM) associated or not for 24 h and 48 h with ethanolic mint extracts used at different concentrations (25, 50, 100, 200 and 400 µg/mL). Under treatment with 7KC, an important inhibition of cell growth was revealed with the crystal violet test. This side effect was strongly attenuated in a dose dependent manner with the different ethanolic mint extracts, mainly at 48 h. The most important cytoprotective effect was observed with the MS extract. In addition, the effects of ethanolic mint extracts on cytokine secretion (Interleukin (IL)-6, IL-10, Monocyte Chemoattractant Protein (MCP)-1, Interferon (IFN)-ϒ, Tumor necrosis factor (TNF)-α) were determined at 24 h on lipopolysaccharide (LPS, 0.2 µg/mL)-, 7KC (20 µg/mL)- and (7KC + LPS)-treated RAW 264.7 cells. Complex effects of mint extracts were observed on cytokine secretion. However, comparatively to LPS-treated cells, all the extracts strongly reduce IL-6 secretion and two of them (MP and MR) also decrease MCP-1 and TNF-α secretion. However, no anti-inflammatory effects were observed on 7KC- and (7KC + LPS)-treated cells. Altogether, these data bring new evidences on the potential benefits (especially antioxidant and cytoprotective properties) of Algerian mint on human health.